E-WALLET: MAKE USERS MORE CONSUMPTIVE? - Taofik Hidajat; Nadiyatul Lutfiyah (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
This study aims to determine the differences in consumer behaviour before and after having an e-wallet. The unit of analysis is students by taking a sample of STIE Bank BPD Jateng students. The analytical method used is the Paired Sample T-Test to prove whether there are significant differences. The results of this study indicate that there are differences in consumptive behaviour before and after having an e-wallet.